Selected Resources for Pathology Evaluation of Nonhuman Primates in Nonclinical Safety Assessment. (July 2022) - Bolon, Brad; Everitt, Jeffrey I.
Humans and nonhuman primates (NHPs) share numerous anatomical and physiological characteristics, thereby explaining the importance of NHPs as essential animal models for translational medicine and nonclinical toxicity testing. Researchers, toxicologic pathologists, toxicologists, and regulatory reviewers must be familiar with normal and abnormal NHP biological traits when designing, performing, and interpreting data sets from NHP studies. The current compilation presents a list of essential books, journal articles, and websites that provide context to safety assessment and research scientists working with NHP models. The resources used most frequently by the authors have been briefly annotated to permit readers to rapidly ascertain their applicability to particular research endeavors. The references are aimed primarily for toxicologic pathologists working with cynomolgus and rhesus macaques and common marmosets in efficacy and safety assessment studies.